PENGARUH ORIENTASI KEWIRAUSAHAAN DAN ORIENTASI PASAR TERHADAP KINERJA PEMASARAN KEDAI KOPI MODERN DI MALANG - Heru Utomo; Umi Khabibah; Fatkhur Rochman (Politeknik Negeri Malang, 2022)
This study aims to determine the effect of entrepreneurship orientation and market orientation on marketing performance at Modern Coffee Shops in Malang. This type of research is explanatory research with the population of this study are all managers or business owners of modern coffee shops in Malang. This total population includes all modern coffee shop businesses in Malang where the exact number is not known. This study used a sample of 30 modern coffee shops in Malang which were taken randomly with cluster sampling technique. From the results of data collection using a questionnaire and analyzed using Multiple Linear Regression analysis, the results obtained are Entrepreneurship Orientation and Marketing Performance have a significant effect on is accepted and hypothesis 2, namely Market Orientation partially has a significant effect on Marketing Performance. The results of the analysis of this study have implications that entrepreneurs need to pay attention to policies that support Entrepreneurship Orientation and Market Orientation, to improve Marketing Performance. Bold and proactive innovation and paying attention to changing consumer desires and competitors' strategies must continue to be carried out to achieve better marketing performance.